New and lesser known species of Chrysopetalidae, Phyllodocidae and Syllidae from south California (Phyllodocida, Aciculata, Annelida) - Pleijel, Fredrik; Aguado, Maria Teresa; Rouse, Greg W. (Zootaxa, 2012)
Two species are described from shallow waters in La Jolla in southern California, the chrysopetalid Dysponetus popu-lonectens, new species, and the phyllodocid Pterocirrus burtoni, new species. The syllid Brachysyllis lagunae (Hartman,1961), new combination (previously in Dioplosyllis), and the phyllodocids Eulalia aviculiseta Hartman, 1936, Eulaliagracilior (Chamberlin, 1919), new combination (previously in Steggoa), Pterocirrus montereyensis (Hartman, 1936), andEumida longicornuta (Moore, 1906) are redescribed from types and newly collected specimens. Sige californiensis Chamberlin, 1919 is treated as a nomen dubium. COI sequences are provided for all included species.